Estimation of scattered radiation influence on neutron beams at a calibration laboratory using Monte Carlo simulation of a long counter (Brazilian Journal of Radiation Sciences (BJRS), 2023)
At the Neutron Calibration Laboratory (LCN) of IPEN/CNEN, a 241AmBe source was used to test and calibrate neutron detectors. The neutrons emitted by the source reach the detector as intended, but they also scatter undesirably from the building's floor, ceiling, and walls, leading to indirect detection. A Long Counter (LC) detector was modeled using the MCNPX Monte Carlo code. The objective of this study was to measure the contribution of scattered radiation at the LCN / IPEN, and to determine the fluence rate, at different points in the calibration room at source-to-detector distances of 100 cm and 150 cm; subsequently, the results were compared with those of the Brazilian Laboratory of Metrology of Ionizing Radiation (LNMRI). The results show that the fluence rates of LCN / IPEN are comparable to those of this neutron laboratory for the 100 and 150 cm source-to-detector distances using a 241AmBe source (37 GBq). The results show that the calibration of neutron detectors should be performed at distances less than 100 cm, where the contribution of scattered radiation is within the 40% limit recommended by ISO 8529-1.